Ty1 Mobilizes Subtelomeric Y′ Elements in Telomerase-Negative Saccharomyces cerevisiae Survivors - Maxwell, Patrick H. (American Society for Microbiology, 2004)
When telomerase is inactivated in Saccharomyces cerevisiae, telomeric DNA shortens with every cell division, and cells stop dividing after ∼100 generations. Survivors that form in these senescent populations and resume growing have variably amplified arrays of subtelomeric Y′ elements. We marked a chromosomal Y′ element with the his3AI retrotransposition indicator gene and found that Y′HIS3 cDNA was incorporated into the genome at ∼10- to 1,000-fold-higher frequencies in survivors compared to telomerase-positive strains. Y′HIS3 cDNA mobility was significantly reduced if assayed at 30°C, a nonpermissive temperature for Ty1 retrotransposition, or in the absence of Tec1p, a transcription factor for Ty1. Microarray analysis revealed that Y′ RNA is preferentially associated with Ty1 virus-like particles (VLPs). Genomic copies of Y′HIS3 cDNA typically have downstream oligo(A) tracts, followed by a complete Ty1 long terminal repeat and TYA1 or TYB1 sequences. These data are consistent with the use of Ty1 cDNA to prime reverse transcription of polyadenylated Y′ RNA within Ty1 VLPs. Unmarked Y′-oligo(A)-Ty1 cDNA was also detected in survivors, reaching copy numbers of ∼10(−2) per genome. We propose that Y′-oligo(A)-Ty1 cDNA recombines with Y′ elements at eroding telomeres in survivors and may play a role in telomere maintenance in the absence of telomerase.